(untitled) (Academic Journal of Internal Affairs, 2018)
The professional literature knows about logical, processual, psychic and knowledge theoratical access for the determination of evidence. This paper intends to present first of all the knowledge theoretical access but with addition of other aspects, too. Criminalistic is a recognition activity. One of the most important factors of recognition is knowledge or science. The Platonic definition of knowledge is the proved true faith. (Not to confuse it with religious faith or with any things believed, we could also say conviction instead of that.) The condition of proving can protect us to consider random lucky hits of truth as knowledge.